Judging social rights - King, Jeff (Cambridge : Cambridge University Press, 2012)
"States that now contemplate constitutional reform often grapple with the question of whether to constitutionalise social rights. This book presents an argument for why, under the right conditions, doing so can be a good way to advance social justice. In making such a case, the author considers the nature of the social minimum, the role of the court among other institutions, the empirical record of judicial impact and the role of constitutional text. He argues, however, that when enforcing such rights, courts ought to adopt a theory of judicial restraint structured around four principles: democratic legitimacy, polycentricity, expertise and flexibility. These four principles, when taken collectively, commend an incrementalist approach to adjudication. The book combines theoretical, doctrinal, empirical and comparative analysis, and is written to be accessible to lawyers, social scientists, political theorists and human rights advocates"--
Introduction : aims and methods -- Part I. The Case for Constitutional Social Rights -- The case for social rights -- The value of courts in light of the alternatives -- A basic interpretive approach -- Part II. A Theory of Judicial Restraint -- Institutional approaches to judicial restraint -- Democratic legitimacy -- Polycentricity -- Expertise -- Flexibility -- Part III. Incrementalism -- Incrementalism as a general theme.
Includes bibliographical references (pages [328]-355) and index.
Keywords: Social rights -- United States; Judicial power -- Social aspects -- United States; Constitutional law -- United States; Political questions and judicial power -- United States; Social justice -- United States; Social rights -- Philosophy; LAW / Constitutional